2009
DOI: 10.1371/journal.pone.0007521
|View full text |Cite
|
Sign up to set email alerts
|

The Pentameric Vertex Proteins Are Necessary for the Icosahedral Carboxysome Shell to Function as a CO2 Leakage Barrier

Abstract: BackgroundCarboxysomes are polyhedral protein microcompartments found in many autotrophic bacteria; they encapsulate the CO2 fixing enzyme, ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO) within a thin protein shell and provide an environment that enhances the catalytic capabilities of the enzyme. Two types of shell protein constituents are common to carboxysomes and related microcompartments of heterotrophic bacteria, and the genes for these proteins are found in a large variety of bacteria.Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 33 publications
6
124
0
Order By: Relevance
“…Basic concepts inherent in early models of carboxysome organization and function (88)(89)(90) have largely been borne out by structurefunction analyses. Reinhold and coworkers' most developed model specifically placed the CO 2 diffusion resistance function at the carboxysome shell (88), and this function was subsequently confirmed in both ␣-and ␤-carboxysomes (19,(91)(92)(93)(94). Similarly, current models of carboxysomal CA localization, where CA nuclei are present throughout the shell structure (95)(96)(97)(98)(99), are consistent with one model version (88) in which numerous "CA sites" are surrounded by "RubisCO zones" rather than carboxysomes which contain a monolithic CA core.…”
Section: Critical Role For Carboxysomesmentioning
confidence: 65%
“…Basic concepts inherent in early models of carboxysome organization and function (88)(89)(90) have largely been borne out by structurefunction analyses. Reinhold and coworkers' most developed model specifically placed the CO 2 diffusion resistance function at the carboxysome shell (88), and this function was subsequently confirmed in both ␣-and ␤-carboxysomes (19,(91)(92)(93)(94). Similarly, current models of carboxysomal CA localization, where CA nuclei are present throughout the shell structure (95)(96)(97)(98)(99), are consistent with one model version (88) in which numerous "CA sites" are surrounded by "RubisCO zones" rather than carboxysomes which contain a monolithic CA core.…”
Section: Critical Role For Carboxysomesmentioning
confidence: 65%
“…Genetic studies in several systems showed that a known pentamer or a pentamer homolog is required for MCP formation in vivo (48,58,72). In another study, the pentameric protein, CsoS4, of the ␣-carboxysome was not absolutely required for shell assembly but was required for shell closure and integrity (73). In another case, a conflicting result was initially obtained with regard to a pentamer homolog encoded by the eut operon.…”
Section: Pentamers Occupy the Vertices Of The Mcp Shellmentioning
confidence: 99%
“…Coenzyme B 12 A complex organometallic cofactor associated with enzymes central to the degradation pathways of ethanolamine and 1,2-propandiol. …”
Section: Pf03319 Domainmentioning
confidence: 99%